2020
DOI: 10.14423/smj.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor-Related Pulmonary Toxicity: Focus on Nivolumab

Abstract: This review article focuses on all pulmonary adverse effects of programmed death-1 (PD-1) inhibitors (nivolumab). These complications include dyspnea, pneumonitis, pleural effusion, pulmonary sarcoidosis, pulmonary tuberculosis, acute fibrinous organizing pneumonia, organizing pneumonia, eosinophilic pneumonia, adult respiratory distress syndrome, and lung cavitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…At present, immune checkpoint inhibitors represent highly promising therapeutic strategies, also for cSCC. They may, however, not apply for all patients due to limitations because of side effects as well as therapy resistance [ 60 ]. Thus, new and additional anticancer strategies are still needed, which may also be used in combinations to improve efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…At present, immune checkpoint inhibitors represent highly promising therapeutic strategies, also for cSCC. They may, however, not apply for all patients due to limitations because of side effects as well as therapy resistance [ 60 ]. Thus, new and additional anticancer strategies are still needed, which may also be used in combinations to improve efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although moist rales/crackles are not very commonly manifested symptoms in the patients with immune checkpoint inhibitor-related pneumonitis, they has been listed as one of the clinical findings suspecting the onset of severe pneumonitis recommending a chest CT (21,22). Furthermore, we demonstrated that in NSCLC patients, the incidence of symptomatic pneumonitis induced by atezolizumab plus chemotherapy was lower in the group also treated with bevacizumab than in the group without bevacizumab.…”
Section: Discussionmentioning
confidence: 62%
“…Respiratory toxicity with checkpoint inhibitors is well documented with a wide range of toxicities reported including dyspnoea, pneumonitis, pleural effusion, pulmonary sarcoidosis, acute fibrinous organizing pneumonia, eosinophilic pneumonia, adult respiratory distress syndrome, and lung cavitation [ 8 , 9 ]. The most common is pneumonitis with a reported incidence of 1.7% of any grade in melanoma with single-agent anti-PD-1 agents [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common is pneumonitis with a reported incidence of 1.7% of any grade in melanoma with single-agent anti-PD-1 agents [ 6 ]. Exacerbation of asthma has been reported and may be fatal [ 8 , 10 ]. Predictive markers for immune checkpoint-related toxicity are lacking.…”
Section: Discussionmentioning
confidence: 99%